Crime and the Regional Disparities in Tourist Inflows: A Case Study of South Africa - Moyo, Busani (Journal of Economics and Behavioral Studies, 2013)
The aim of this study is to investigate the impact of crime proxied by different indicators on regional tourist inflows to South Africa. The estimations are carried out using the Johansen estimation techniques. Monthly data gathered from March 2003 to April 2011 is employed and the results from the estimations found that total crime has a negative effect on tourists from Africa, North America, Central and Southern America, West and Southern Europe. However, the level of crime in the country appears to have no influence at all to tourist from the Middle East whilst those from Asia are more sensitive to the level of sexual crime. At the different categories of crime investigated, tourists react differently. In line with the findings of the existing literature, the real exchange rate and world income remain to have a significant effect on tourist inflows from most of the regions.